2018
DOI: 10.1108/bepam-10-2017-0091
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency practices for Malaysian green office building occupants

Abstract: Purpose Green building construction was adopted as a strategy to reduce energy consumption and the overall impact of the built environment on our natural environment. However, in Malaysia, previous studies have reaffirmed that green office buildings consume a substantial amount of energy, compared to their counterparts in Singapore. Moreover, there is still a significant performance gap between predicted energy measurements and actual operational energy consumption of green office buildings in Malaysia, due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…This implied that electrical energy conservation in the city offices was based on efficient energy usage, where the use of electricity was being monitored on a quarterly basis so as to check whether it has decreased or not. The monitoring approach is a form of control system that can effectively influence energy consumption reduction so as to realise green office buildings (Ohueri et al 2018). Interviews drawn from the informants indicated that the Surakarta city had implemented measurements to audit its energy consumption.…”
Section: Dimension Of Electrical Energy Conservationmentioning
confidence: 99%
See 2 more Smart Citations
“…This implied that electrical energy conservation in the city offices was based on efficient energy usage, where the use of electricity was being monitored on a quarterly basis so as to check whether it has decreased or not. The monitoring approach is a form of control system that can effectively influence energy consumption reduction so as to realise green office buildings (Ohueri et al 2018). Interviews drawn from the informants indicated that the Surakarta city had implemented measurements to audit its energy consumption.…”
Section: Dimension Of Electrical Energy Conservationmentioning
confidence: 99%
“…Sustainable building materials that are integrated with technological strategy has the potential to strategically reduce the energy consumption of these buildings (Ohueri et al 2018). Since lighting is one of the important factor enabling human beings to conduct their daily activities, lighting engineering and its planning for buildings play an important role (Setiawan and Hartanti 2014).…”
Section: Dimension Of Building and Spatial Structurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, in [14] conducted comment on Green Building Index(GBI) in Malaysia while review on other green building assessment systems are not conducted. Besides that, in [22] focused only on GBI and the research did not focus on other assessment systems such as MyCREST because the researchers stated that MyCREST is still fresh in Malaysia. There is a lack of research conducted to make comparison between green building assessment systems in Malaysia.…”
Section: Ong Boon Zian Soo-fen Fam Chuanzun Liang Sentot Imam Wahjmentioning
confidence: 99%
“…Performance Analysis during the decision-making cycle improves design to ensure an optimized project with better environmental effectiveness (OHUERI et al, 2018); (OLAWUMI et al, 2018).…”
Section: 12building Performancementioning
confidence: 99%